Networks and labor market entry – a historical perspective. (1st January 2017) - Håkansson, Peter; Tovatt, Caroline
Abstract: This paper discusses how recruitment practices have changed over time. Networks and contacts are more important today for labor market entry than was the case in the latter half of the twentieth century. There may be two explanations for this: the short-run explanation and the long-run explanation. The short-run explanation derives from fluctuations in unemployment. When unemployment is high, competition for every vacancy is tougher and networks become more important for the job seeker. This has been the case in Sweden since 1991, when unemployment increased to new levels not experienced since the 1930s. In the long run, there has been a change in recruitment practices due to institutional change. A clear pattern is that the importance of social networks has increased, while the significance of public institutions (i.e. the Public Employment Service) has decreased.